2010
DOI: 10.1590/s1516-635x2010000100009
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive characteristics of captive greater rhea (Rhea americana) males reared in the state of São Paulo, Brazil

Abstract: Rheas (Rhea americana) belongs to the ratite group. Considering the commercial significance of this birds, some techniques, such as semen collection, were standardized. In this study, 107 male rheas (3 to 4 years of age) reared in commercial farms in the state of São Paulo, Brazil, were used. Semen was collected during the breeding and offbreeding seasons of 2001, 2002, and 2003. Bird hierarchical behavior was observed. Birds were restrained performed using a box and a black hood. Semen was collected by digita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 10 publications
2
16
2
1
Order By: Relevance
“…Reporting on the incidence of abnormal sperm in the emu, Malecki et al [24] provide a category for "bent sperm" without defining the term whereas Góes et al [25] simply report that bent heads, folded tails and strongly folded tails are observed in the rhea. Midpiece reflexes have been described in the ostrich [26,27] and Soley et al [28] reported an association between cytoplasmic droplets and bent tails in the same species.…”
Section: Introductionmentioning
confidence: 99%
“…Reporting on the incidence of abnormal sperm in the emu, Malecki et al [24] provide a category for "bent sperm" without defining the term whereas Góes et al [25] simply report that bent heads, folded tails and strongly folded tails are observed in the rhea. Midpiece reflexes have been described in the ostrich [26,27] and Soley et al [28] reported an association between cytoplasmic droplets and bent tails in the same species.…”
Section: Introductionmentioning
confidence: 99%
“…The breeding season of Rhea americana is in the spring (Immelmann, 1971) and summer, starting in the first warm days of late winter and finishing mid-February (Góes et al, 2010) at 30 • S. In the present study, the animals started the reproductive season in July and stopped in December. This might be because the animals were closer to the equator (25 • S).…”
Section: Discussionmentioning
confidence: 63%
“…Although the farm breeding of Rhea americana began around 1800, studies of its reproductive behavior have been rare (De Almeida, 2003), mainly comparing it to other species of ratites (flightless birds), such as the ostrich (Góes et al, 2010). Rhea americana initiates reproductive activity as the photoperiod increases, varying according to the latitude (Cubas et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to ontogenetic phallus development, androgen mediated regulation of phallus size may be seasonally dynamic. In Rhea americana , phallus size positively correlated with circulating testosterone levels between breeding and non‐breeding seasons (Goes et al,2010). Therefore, the phallic morphologies presented in this manuscript are of a developing juvenile anatomy which will greatly enlarge and elaborate with increased exposure to sex hormones and sexual maturity.…”
Section: Discussionmentioning
confidence: 99%